The Role Of Human Development In Economic Growth And Poverty Reduction In Bener Meriah Regency - Mirantika Mirantika; Rusiadi Rusiadi; Lia Nazliana Nasution; Bhaktiar Efendi; Suhendi Suhendi (International Journal of Science and Environment (IJSE), 2025)
This study aims to examine the interrelationship between economic growth and poverty in Bener Meriah Regency by employing a simultaneous equations modeling approach. Two main structural equations were developed: the first evaluates the influence of unemployment, the Human Development Index (HDI), and poverty on economic growth; the second investigates the impact of expected years of schooling (EYS), labor force participation, and economic growth on poverty levels. The estimation results reveal that HDI and poverty significantly affect economic growth, while unemployment shows no statistically significant influence. In the second equation, educational attainment (as measured by EYS) and economic growth are found to be significant factors in reducing poverty, whereas the labor force variable does not exhibit a meaningful effect.These findings underscore the pivotal role of human development—particularly in the domains of education and decent living standards—as a fundamental driver of inclusive economic growth and sustainable poverty alleviation. The study offers valuable insights for regional development policy, emphasizing the need to invest in human capital and enhance the quality of the local workforce. By adopting a simultaneous modeling framework, this research provides a strategic reference for designing holistic and socially equitable development policies, especially in rural regions such as Bener Meriah.